Practice and Reflection on Socialist Thought with Chinese Characteristics in the New Era in College Education - Fan, Linji (International Journal of Social Sciences and Public Administration, 2024)
Higher education, as a key area for cultivating high-quality talents and future socialist builders, must comprehensively and deeply implement the Socialist Thought with Chinese Characteristics for the New Era, and continue to explore and optimise it in practice to meet the needs of the times. At the practical level, colleges and universities across the country have actively responded to the call of the Party and the government to deeply promote the wide dissemination of the Socialist Thought with Chinese Characteristics for a New Era on campuses and the deepening of people’s hearts through multiple dimensions such as reform of the on-campus curriculum system, construction of teaching staff, and ideological and political education of students. Colleges and universities have endeavoured to build a comprehensive education system covering philosophy and social sciences as well as natural sciences, and to strengthen national awareness, historical awareness, and cultural self-confidence, so as to make them the cornerstones of students’ learning and growth. At the level of thinking, educators and university administrators generally agree that the effective internalisation and educational practice of socialist thinking with Chinese characteristics in the new era requires the refreshing of classroom teaching content, the innovation of teaching methods and the creation of campus culture. In addition, emphasising the cultivation of students’ critical thinking and independent thinking, and continuously improving their ability to solve real-world problems are also key in educational practice. This not only requires teachers to impart knowledge, but also focus on guiding students to have a deep understanding and rational evaluation of social phenomena. However, there are many challenges in the practice of socialist thought with Chinese characteristics in the new era in colleges and universities. Such as how to adhere to and develop the road of socialism with Chinese characteristics in the context of globalisation, how to strengthen and improve the ideological and political work of colleges and universities under the conditions of the market economy, and how to better solve the problem that the mechanism of nurturing people in colleges and universities is not adapted to the needs of social development, etc., which all need our in-depth thinking and active exploration of the solutions. In the future, the practice of Socialist Thought with Chinese Characteristics in the new era in college education will pay more attention to cultivating students’ practical ability and innovation ability, pay more attention to the inheritance and promotion of traditional culture, and put more emphasis on humanistic care and whole-person education in education. Through such practice and thinking, it will not only provide intellectual support and talent guarantee for the development of university education and the cause of socialism with Chinese characteristics, but also create a broader space for the comprehensive development of all students and the realisation of their personal dreams.